المعالجة المثلى للإشارات في نظم الإرسال الرقمية بوجود الضجيج الجمعي والتشويه الخطي ( الطرائق الخطية ) - أحمد صقر أحمد (Tishreen University, 2019)
تعتبر الحاملة الراديوية ( Carrier ) الركن الأساسي الذي يُعتمد عليه في عملية نقل المعلومات الرقمية, حيث تمثل الجزء المعلوم من الإشارة الكلية بعد تحميلها بالمعلومات الرقمية العشوائية وتعرضها لمختلف أنواع الضجيج والتداخل والمعوقات الأخرى. يعتمد هذا البحث على إيجاد الشكل الأفضل ( الشكل المثالي ) للحاملة الراديوية في النظم الرقمية من خلال التحليل الرياضي للنظام بشكل عام ودراسة توابع النقل المختلفة لعناصر النظام واستنتاج تابع النقل المثالي لمرشح الاستقبال الذي يستطيع استخلاص الحاملة الراديوية مع إشارة المعلومات بشكل سليم رغم وجود الضجيج الأبيض ( ضجيج غاوص ) وضجيج التداخل الناتج عن عدم الوفاء بشرط شانون ونايكويست. يعتمد البحث على استخدام الشكل الرياضي الناتج كأساس لإجراء المقارنة مع الحاملة الراديوية التي تستخدم النبضة المستطيلة بعد وضع أنموذج يحاكي الشكل العملي لتابع نقل قناة الاتصال وإمكانية التحكم بشكل مرشح التمرير والمرسل, ومن ثم مقارنة النتائج ومناقشتها اعتماداً على قيم الضجيج الجمعي وقيم الضجيج الناتجة عن عملية التداخل. The carrier signals represent the basic base on which we depend in the process of digital information transmission. They represent the familiar part of the whole signal after loading it with random digital information and exposing it to different kinds of noise, interference and other obstacles. This paper aims to optimize form (ideal form) of the carrier signal in the digital system, generally using the statistical analysis of the system to study the different transmission functions of the elements and to select the ideal transaction function of the receiving filter, which can positively select the carrier signal, together with information signal in spite of the existence of white noise (Gauss's Noise) and interference noise as a result of deviation from the basic  cycle time. The paper uses the resultant mathematical form as a base to make the comparison with the carrier signal, which uses rectangular pulse after adopting a form that represents the practical form of the transaction function of the communication channel and the possibility of controlling the form of passing filter and transmitter. It then compares and discusses the results by ratio and identifies ways of reducing noise and interference.